Effect of Cryogenic Treatment on Friction and Wear Properties of 20CrNiMo Carburized Steel - LI Min, NI Lei, XIANG Beiping (Cailiao Baohu, 2022)
In order to improve the friction and wear properties of 20CrNiMo carburized steel, the cryogenic treatment was carried out on it for different durations and different cycles. The changes of microstructure, hardness and impact toughness before and after cryogenic treatment were analyzed by means of scanning electron microscope and Rockwell hardness tester. The friction and wear properties of samples before and after cryogenic treatment were compared and investigated by friction and wear testing machine. Results showed that the cryogenic treatment had a limited effect on the surface hardness of 20CrNiMo carburized steel. The impact toughnesses of the samples were significantly improved after cryogenic treatment, and the impact toughness was the highest when the sample was treated with a single cycle of 6 h cryogenic treatment, which was increased by 10.9% compared with the un - cryogenic sample (QT). The average friction coefficient and relative wear rate of cryogenic samples were significantly reduced. The samples treated with a single cycle of 6 h cryogenic treatment and 3 cycles of 3 h cryogenic treatment had better friction and wear properties, and the average friction coefficient were 0.50 and 0.52 respectively. Compared with the QT samples, the wear rates were reduced by 25.9% and 23.3% respectively.